Effects of dietary counselling on lipid profile among liposuction patients - Jehan , Adeela; Ahmed , Zaheer; Kashif, Seemin; Liaqat , Saba; Mohmand, Humayun; Afreen, Asma (Journal of the Pakistan Medical Association, 2023)
Objective: To observe the effects of dietary counselling on weight management after liposuction. Method: The case-control study was conducted at the La Chirurgie Cosmetic Surgery Centre and Hair Transplant Institute, F-8/3, Islamabad, Pakistan, from January to July 2018, and comprised adults (100) of either gender undergoing liposuction and/or abdominoplasty who were followed for three months in the postoperative period. The subjects were divided into dietary-counselled group A, which received diet plans, and control group B, which followed up without any dietary advice. Lipid profile was done at baseline and three months post-liposuction. Data was analysed using SPSS 20. Results: Of the 100 subjects enrolled, 83(83%) completed the study; 43(51.8%) in group A and 40(48.2%) in group B. Overall, there were 19(22.9%) males, 64(77.1%) females, and 55(66.3%) were aged <40 years, while 28(33.7%) were aged 40 years. Intra-group improvement was significant for total cholesterol, low-density lipoprotein, and triglycerides for both the groups (p<0.05). The change for very low-density lipoprotein in group B was not significant (p>0.05). Change in high-density lipoprotein was for the better in group A, while it decreased in group B and the change in both cases was significant (p<0.05). Inter-group differences were not significant (p>0.05) except for total cholesterol (p<0.05). Conclusion: Liposuction alone resulted in the improvement of lipid profile, while dietary intervention resulted in better values with respect to very low-density lipoprotein and high-density lipoprotein. Key Words: Liposuction, Diet, Dietary Counselling, Cholesterol, HDL, LDL, Triglycerides.